Pengembangan E-Module Pendukung PBL Terintegrasi Potensi Lokal Yogyakarta pada Materi Perubahan Lingkungan untuk Meningkatkan Literasi Lingkungan dan Kemandirian Belajar Siswa - Dumaris Taruli Artha Siahaan; Paidi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop a Problem Based Learning (PBL)-supported e-module integrated with Yogyakarta local potential on environmental change materials that is valid, practical, and effective in improving students’ environmental literacy and self-regulated learning. The method used was Research and Development (R&D) with stages of analysis, design, development, implementation, and evaluation. The subjects of this study were 72 phase E students at SMAN 1 Depok Sleman. Data were collected through biology teacher interviews, student needs analysis, material and media expert validation questionnaires, practicality questionnaires for teachers and students, environmental literacy tests, and self-regulated learning questionnaires. The data were analyzed using descriptive and inferential statistics through MANOVA and bivariate correlation tests. The results showed that the developed e-module met the criteria of validity, practicality, and effectiveness for learning implementation. The use of the e-module contributed to improving students’ environmental literacy and self-regulated learning and demonstrated a relationship between both variables. In conclusion, the PBL-supported e-module integrated with Yogyakarta local potential can be used as teaching material to support the improvement of environmental literacy and students’ self-regulated learning. Keywords: Environmental Literacy, Local Potential of Yogyakarta, PBL, Self-Regulated Learning, E-Module